2022
DOI: 10.13189/saj.2022.100209
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Training Methods and Explosion of Limb Muscles on Pencak Silat Kicking Skills

Abstract: The purpose of this study was to determine the best training method between plyometrics, circuit training methods, and continuous training methods, which had more effect on improving the results of Pencak Silat kick skills training. The method used in this study is an experimental method (comparative quantitative) with a 3 x 2 factorial design. The number of samples in this study was 56 students of the Health Sports Education Study Program of STKIP Setia Budhi Rangkasbitung in the Pencak Silat course, with a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Other research also reported that plyometric training significantly affects the momtong dollyo Chagi Kick of junior taekwondo athletes [21]. There was also an improvement in kicking performance in Pencak silat after conducting plyometric training [13]. It means that with the quality of leg muscle power, the kicking performance in martial art sports, including Pencak silat, will positively and strongly correlate.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Other research also reported that plyometric training significantly affects the momtong dollyo Chagi Kick of junior taekwondo athletes [21]. There was also an improvement in kicking performance in Pencak silat after conducting plyometric training [13]. It means that with the quality of leg muscle power, the kicking performance in martial art sports, including Pencak silat, will positively and strongly correlate.…”
Section: Discussionmentioning
confidence: 86%
“…There is much previous research concerning Pencak silat, such as training methods to improve the capacity of cardiovascular endurance of the Pencak silat athlete [9], to improve core strength muscle, and dynamic balance [10]. Besides that, there is also research related to the leg muscle power effect on cycle kick performance [11], the leg muscle power effect on straight kick skill [12], and the training method that has a significant effect on Pencak silat kicking skill [13].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study in the Province of Banten in Indonesia, in a match the foot attack technique (sickle kick) was the most dominant and was often used to get points (Sudirman et al, 2022). This statement was also reinforced by Amrullah in his research showing that 90% of points were obtained through kick attacks (Amrullah, Dlis, & Hernawan, 2020).…”
Section: Introductionmentioning
confidence: 91%
“…Pencak Silat is a contemporary umbrella term used in Indonesia, Malaysia, and other Southeast Asian countries to refer to hundreds of traditional and modern martial arts practiced either by single players or duels, with or without background music (Hadiana, 2022). Pencak means Search, Silat means Gathering, when the two meanings of the word are combined, Pencak Silat means Searching for Gathering (Sudirman et al, 2022). Then it expanded in all directions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation